(untitled) (Texas Journal of Engineering and Technology, 2024)
Today, the Ustyurt gas chemical plant in our Republic is not processing a large amount of byproduct waste, which has a negative influence on the environment. The composition of these wastes was studied by vacuum fractionation at high temperature, and the obtained products were analyzed by physico-chemicall. Polymethyleneanthacene sulfoacids (SOF-1 and SOF-2) with a spatial structure were synthesized by polycondensation of the obtained mono- and dianthracene sulfoacids with formalin. Process parameters were studied.